The beneficial effects of S-methyl-methionine in maize in the case of Maize dwarf mosaic virus infection - Ludmerszki, Edit (Acta Biologica Szegediensis, 2011)
Maize dwarf mosaic virus (MDMV) is one of the most common pathogens infecting maize plants. Its infection causes decreased plant growth and chlorotic bands on the leaves giving a mosaic pattern. Our efforts aimed to increase the plants’ inherent resistance with exogenic addition of the natural compound S-methyl-methionine (SMM) that plays a central role in the plant sulphur metabolism. SMM is a key compound in various metabolic pathways connected with resistance mechanisms of several stresses. In the present study Jubilee sweet corns were used, on which the harmful effects of MDMV and the advantageous actions of SMM were recorded applying non-invasive fluorescence imaging and induction methods and DAS-ELISA test. According to the results, the SMM treatment improved the physiological parameters of the maize plants (including photosynthetic rate and the amount of chlorophyll pigments), and nevertheless it significantly improved the plants’ defence response to viral infection.